Partisipasi Politik Waria Dalam Pilkada DKI Jakarta Tahun 2017 - Baskoro Adi, Septian Tri; Erowati, Dewi (Journal of Politic and Government Studies, 2019)
The democratic party called Pemillihan Kepala Daerah or Pilkada is a form of popular sovereignty to elect leaders in the region, DKI Jakarta Province is one of the regions that held the simultaneous Regional Election in 2017. The DKI Jakarta Election 2017 is not only followed by majority but also minorities, one of them is wanita-pria or commonly called waria. The number of transvestites who are only in the thousands makes this group a minority in the democratic party and vulnerable to existing discrimination. The level of participation of transgender groups is interesting to study because of the large number and plurality of the people of DKI Jakarta as well as the politics of DKI Jakarta which has become a barometer of democracy in Indonesia. This study uses a mixed method research method to combine descriptive and quantitative descriptive qualitative data and use Huntington and Nelson's political participation theory. The results of this study are to describe various forms of political participation of transgender groups in the DKI Jakarta Pilkada in 2017 according to Huntington and Nelson's political participation theory. The conclusion of this study shows the low level of political participation of transgender groups which are influenced by internal and external factors.Keywords: Local election, Participation, Politics, Transgender Keywords: Local election, Participation, Politics, Transgender